Developmental aspects of synaesthesia across the adult lifespan - Meier, Beat; Rothen, Nicolas; Walter, Stefan (Frontiers in Human Neuroscience, 2014)
In synaesthesia, stimuli such as sounds, words or letters trigger experiences of colours, shapes or tastes and the consistency of these experiences is a hallmark of this condition. In this study we investigate for the first time whether there are age-related changes in the consistency of synaesthetic experiences. We tested a sample of more than 400 grapheme-colour synaesthetes who have colour experiences when they see letters and/or digits with a well-established test of consistency. Our results showed a decline in the number of consistent grapheme-colour associations across the adult lifespan. We also assessed age-related changes in the breadth of the colour spectrum. The results showed that the appearance of primary colours (i.e., red, blue, and green) was mainly age-invariant. However, there was a decline in the occurrence of lurid colours while brown and achromatic tones occurred more often as concurrents in older age. These shifts in the colour spectrum suggest that synaesthesia does not simply fade, but rather undergoes more comprehensive changes. We propose that these changes are the result of a combination of both age-related perceptual and memory processing shifts.